Simultaneous extraction of hydrocarbons and heavy metals from contaminated soils. - Han, Xu (Curtin University, 2000)
Soil Washing is a promising alternative treatment method for contaminated site remediation. An industry contaminated site - the OMEX site was selected for the study, and several extraction additives (chelating agent and surfactant) were used to investigate the application of soil washing for the removal of heavy metals and hydrocarbons. The interactions and transport of the contaminants were studied by bench-scale experiments for both heavy metals and hydrocarbons. Soil characterization was performed before the experiments.The soil characterization indicated that the OMEX soil contained large amounts of Pb, Zn (heavy metal) and total petroleum hydrocarbons (TPH). The contaminant concentrations were 986 mg/kg of Pb, 284 mg/kg of Zn, and 29000 mg/kg of TPH. The contaminated soil was also high in moisture content, organic content and total organic carbon (TOC). From soil analyses on different particle size fractions, most contaminants were concentrated in the fine soil fraction, below 150gm, which constituted about 35% by weight of the contaminated soil.Heavy metal removal by chelating agents was conducted first. The results showed that 3% EDTA solution offered the highest removal efficiency for both Pb and Zn. About 90% of Pb and 65% of Zn were removed by using 3% EDTA solution for 29 hours. The extraction kinetics proved to be slow, reaching equilibrium in a relatively long time (more than 10 hours). In soil washing the solution pH had some effect on the removal of both Pb and Zn with marginally better removals observed at a lower pH. The experimental study indicated that the ratio of washing solution volume to soil weight (LIS) had little effect on the percentage removal of both Pb and Zn.In hydrocarbons removal tests, experiments verified that surfactant solutions can be effective in removing organics from coarse soil fraction, while some amount of surfactants were adsorbed by fine soil particles. Anionic surfactants such as SIDS exhibited less sorption capacity than nonionic surfactants due to the electrostatic repulsion of the former. 4% SDS solution had the highest TPH removal efficiency for OMEX soil, but the 2% SIDS solution was used as it produced only marginally lower results than the 4%. The percentage removal of TPH was about 78% by using 2% SIDS solution. The TPH removal by SDS solution was observed to be a slow and non-equilibrium process. Higher solution temperature can improve removal efficiency of TPH from OMEX soil. Combined washing with a chelating agent and a surfactant was effective in removing both heavy metals and hydrocarbons. Removals of 78% Pb, 82% Zn and 81% TPH were obtained from OMEX soil in the combination test. However, the TPH concentration in fine soil was still very high after washing and would need further treatment.